Cryptocurrencies Versus Gold: Safe-Haven Competition - Mselmi, Aymen; Mahmoud, Imen (International Journal of Economics and Financial Issues, 2024)
This study investigated the impact of the COVID-19 pandemic on two cryptocurrencies, Bitcoin and Ethereum, on the one hand, and gold, on the other hand. We analysed a large dataset from 13 countries worldwide. This study aimed to identify a reliable safe haven for investors during a health crisis. Our results indicated a positive association between Bitcoin and Ethereum prices and the COVID-19 variables. However, the relationship between gold prices and COVID-19 health indicators differed among countries, with inconsistent results.